Tinkering with nature: craft, domesticity and female labour in F Percy Smith’s ‘Data’ notebooks (1925–1944) - Max Long (Science Museum Group Journal, 2023)
This article examines two notebooks belonging to the scientific filmmaker F Percy Smith, labelled ‘Data A’ and ‘Data B’, which are held at the National Science and Media Museum (NSMM) in Bradford. These notebooks offer valuable insights into Smith’s working process in the last two decades of his life – between 1925 and 1945 – and they detail the wide array of materials, tools and equipment that he used to produce his films. The article suggests some of Smith’s uses for the notebooks, such as noting down locations for collecting specimens or describing how to construct tanks and troughs for filming individual organisms. Using a wide range of supplementary sources, including images, videos and an interactive map, I argue that Smith’s work amounted to a form of scientific ‘craft’, which blended across his experimentation with photographic media and scientific observation. Dismantling the long-held belief that F Percy Smith worked entirely alone, the article uses the notebooks as an opportunity to highlight for the first time the role that two women played in Smith’s studio-laboratory: his wife, Kate Smith, and his assistant, Phyllis Bolté. The notebooks are a key source for understanding the production of natural history films of the interwar period, including the popular Secrets of Nature (1922–1933) series. The article reflects on what media scholars can learn from taking a closer look at the materials and methods used for making films of this kind.